Building Sustainable Competitive Advantage through the Green School Program: A Resource-Based View Case Study of Educotourism School Management - Imam Basofi; Munirul Abidin; Samsul Susilawati (Universitas Nurul Jadid, 2025)
Schools increasingly compete for enrollment, reputation, and public trust, yet whether an environmental program can function as a strategic resource for building competitive advantage remains underexamined in the madrasah context. This study analyzes how the Green School program at MTs Negeri 3 Pamekasan, developed through the Educotourism School concept, builds sustainable competitive advantage across three foci: the underlying concept, the implementation strategy, and the contribution to institutional standing. A qualitative single case study design was employed, drawing on purposive sampling across four informant categories, in-depth interviews, participant observation, and documentary review, analyzed through thematic analysis with source and technique triangulation. Findings show the program integrates education, ecology, and tourism into one coherent system, implemented through six connected components spanning policy, curriculum, and community partnership, and contributing to institutional reputation, academic achievement, and local economic empowerment. Read through the resource-based view, the program satisfies the VRIN criteria through resources embedded in a specific geography and decades of village trust that competitors cannot relocate or purchase. The study carries direct implications for educational management: school leaders seeking durable competitive advantage should treat environmental programs as strategic investments rather than compliance exercises, and should deliberately cultivate relational resources with surrounding communities alongside internal policy and curriculum development.